2009
DOI: 10.5194/hess-13-2349-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in soil active-layer geochemistry across hydrologic margins in polar desert ecosystems

Abstract: Abstract. Polar deserts are characterized by severe spatialtemporal limitations of liquid water. In soil active layers of the Antarctic Dry Valleys, liquid water is infrequently available over most of the arid terrestrial landscape. However, soils on the margins of glacial melt-water streams and lakes are visibly wet during the brief Austral summer when temperatures permit the existence of liquid water. We examined the role of these hydrologic margins as preferential zones for the transformation and transport … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…With the exception of the Miers lake sample (which was most likely formed by "evapoconcentration" whereby lake water evaporates near the soil surface and concentrates lake-derived salts in the upper soil column [Barrett et al, 2009]), the salts rich in bicarbonate/carbonate are found in the eastern (coastal) region of TV near streams. Bicarbonate/carbonate salts are not found west of the Fryxell basin, which is consistent with the findings of Claridge and Campbell (1977) because a lower pH in soils westward is attributed to the accumulation of alkaline marine aerosols near the coast and acidic aerosols near the East Antarctic Ice Sheet.…”
Section: Co 3 /Hco 3 Saltsmentioning
confidence: 99%
“…With the exception of the Miers lake sample (which was most likely formed by "evapoconcentration" whereby lake water evaporates near the soil surface and concentrates lake-derived salts in the upper soil column [Barrett et al, 2009]), the salts rich in bicarbonate/carbonate are found in the eastern (coastal) region of TV near streams. Bicarbonate/carbonate salts are not found west of the Fryxell basin, which is consistent with the findings of Claridge and Campbell (1977) because a lower pH in soils westward is attributed to the accumulation of alkaline marine aerosols near the coast and acidic aerosols near the East Antarctic Ice Sheet.…”
Section: Co 3 /Hco 3 Saltsmentioning
confidence: 99%
“…In a process that has been termed "evapoconcentration," this lake water evaporates near the soil surface, concentrating salts dissolved in the lake water into the upper soil . Soluble salts in soils influenced by evapoconcentration have been sampled by Barrett et al [2009] to 10 cm depth. Clconcentrations in these soils average about 100 mmol Clkg -1 .…”
Section: Taylor Valley Paleolakesmentioning
confidence: 99%
“…Clconcentrations in these soils average about 100 mmol Clkg -1 . Using this Clconcentration and an average bulk density of about 1.65 g cm -3 as measured by Barrett et al [2009], the average Clcontent calculated from equation (2) is 16.5 mol Clm -2 . This value is relatively high and is similar to Clcontents measured in Bonney Basin soils, older soils near the Nussbaum Riegel, and soils below approximately 120 m elevation in eastern Taylor Valley.…”
Section: Taylor Valley Paleolakesmentioning
confidence: 99%
See 2 more Smart Citations